"Blir tårögd när staten ifrågasätter min rätt att existera" : En kvantitativ innehållsanalys av SVT och SR:s webbjournalistik och bevakning av Girjasmålet mellan 2015-2019 - Haglund, Johanna; Haglund, Ellen (Högskolan i Jönköping, HLK, Medie- och kommunikationsvetenskap, 2020)
The indigenous people of Sweden, the Sámi, is a people that has been discriminated against ever since the Swedish colonialization of the North in the 14th century. They still experience exclusion and racism to this day and age. A big step towards the decolonization of the North and justice for the Sámi was taken when Girjas sameby sued the Swedish state on the accusation of violating their indigenous rights. This is an issue of high importance to both the Sámi and the Swedish community and should therefore be on the media’s agenda. The aim of the study is to examine the Swedish public service’s coverage of indigenous issues, and the possible differences in coverage between their national, regional and local editorials as well as between their indigenous and Swedish platforms. Retriever Media Archive was used to collect 527 articles, out of which 406 were valid for this case study. The method used to analyze the data is a quantitative content analysis based on the theoretical framework of agenda-setting theory, media logic, media shadow, news values and editorial choices, post-colonial theory, and critical discourse analysis. The most prominent conclusion of this case study is that there is a big difference in how often the case of Girjas is being mentioned in public service’s news coverage. It is most often cited by the indigenous editorial, and the least by the national editorials. This is problematic as a probable risk is that the audience, the Swedish majority, is not receiving vital features of the case. This paper also strives to problematize the exclusion of minority issues in the media. Samerna har levt och verkat i Sápmi långt innan Sverige fick sin landsgräns. Trots detta har de under flera hundra år levt under förtryck av både staten och svenskar. Tyvärr pågår den negativa behandlingen av samer än i dag, trots att de har blivit erkända som ett urfolk av Sveriges riksdag. 2009 valde en sameby, Girjas, att lämna in en stämningsansökan mot svenska staten för att de ansåg att staten inskränkte samernas ...